Development of Biodiversity Practicum E-Module to improve Science Process Skills - Marjanah Marjanah; Teuku Hadi Wibowo Atmaja; Ekariana S. Pandia; Nursamsu Nursamsu; Nurhasnah Manurung (Postgraduate, University of Mataram, 2022)
The learning tools of the biodiversity practicum e-module in lectures using the e-module can be useful and serve as a guide or guide for science process skills activities. The purpose of the pelitian is to study the matter of Creating and Designing Products for Learning Tools E-Module Local Biodiversity to improve Science Process Skills and Conduct Feasibility and Practical Testson e-Modules Practicum Biodiversitas in terms of Cover, Module Design, Language and Material Content. While the method in this study uses the product development method from the e-module in practicum activities in the science process skills process which consists of research stages, namely formulating potentials and problems, collecting data, conducting research product designs, conducting product validation, carrying out product revisions, conducting product trials and continuing product revisions. The results showed in terms of expert validation that the biodiversity practicum e-module is suitable for use while the practicality test given by the questionnaire to students in response to the e- assessment The biodiversity practicum module is very practical to be used in the implementation of the biodiversity practicum